Problem-Solving Ability and Self-Efficacy Based On Geometry Thinking Level In Van Hiele Learning (Unnes Journal of Mathematics Education Research, 2020)
The objectives of this study are to test the effectiveness of van Hiele's learning of students; problem-solving ability and describe their problem-solving ability and self-efficacy based on the level of geometrical thinking. This research was a type of mixed quantitative and qualitative research. The study was conducted at MTs Asy-Syarifah in the 2015/2016 academic year. The research subjects were eighth grade students consisting of one experimental class with treatment using van Hiele learning and one control class. Hypothesis testing used a one-tailed proportion test and an average difference test. The results are obtained that van Hiele learning is effective in students' problem-solving ability. The average score of students who get van Hiele learning is higher than students who get expository learning. Students at level 2 (informal deduction) can reach all indicators of problem-solving. Students at level 2 can carry out the stages of problem-solving according to Polya's steps. Students at level 1 (Analysis), the students have not been able to carry out the completion plan appropriately. Students have difficulty in implementing a problem-solving plan. Students at level 0 (visualization) have not been able to plan properly. The results of the analysis of the three dimensions of students’ initial self-efficacy show that students: (1) still have difficulties and try to avoid difficult tasks, (2) give up easily when facing difficulties.